Trade‐offs across productivity, GHG intensity, and pollutant loads from second‐generation sorghum bioenergy. Issue 12 (11th September 2017) - Fertitta‐Roberts, Cara; Spatari, Sabrina; Grantz, David A.; Jenerette, G. Darrel
Abstract: Greenhouse gas (GHG) intensity is frequently used to assess the mitigation potential of biofuels; however, failure to quantify other environmental impacts may result in unintended consequences, effectively shifting the environmental burden of fuel production rather than reducing it. We modeled production of E85, a gasoline/ethanol blend, from forage sorghum ( Sorghum bicolor cv. photoperiod LS) grown, processed, and consumed in California's Imperial Valley in order to evaluate the influence of nitrogen (N) management on well‐to‐wheel (WTW) environmental impacts from cellulosic ethanol. We simulated 25 N management scenarios varying application rate, application method, and N source. Life cycle environmental impacts were characterized using the EPA's criteria for emissions affecting the environment and human health. Our results suggest efficient use of N is an important pathway for minimizing WTW emissions on an energy yield basis. Simulations in which N was injected had the highest nitrogen use efficiency. Even at rates as high as 450 kg N ha −1, injected N simulations generated a yield response sufficient to outweigh accompanying increases in most N‐induced emissions on an energy yield basis. Thus, within the biofuel life cycle, trade‐offs across productivity, GHG intensity, and pollutant loads may be possible to avoid at regional to global scales. However, trade‐offs were seemingly unavoidable when impacts from E85 were compared to those of conventional gasoline. The GHG intensity of sorghum‐derived E85 ranged from 29 to 44 g CO2 eq MJ −1, roughly 1/3 to 1/2 that of gasoline. Conversely, emissions contributing to local air and water pollution tended to be substantially higher in the E85 life cycle. These adverse impacts were strongly influenced by N management and could be partially mitigated by efficient application of N fertilizers. Together, our results emphasize the importance of minimizing on‐farm emissions in maximizing both the environmental benefits and profitability of biofuels. Abstract : Our results suggest efficient use of N is an important pathway for minimizing WTW emissions on an energy basis. Simulations in which N was injected had the highest nitrogen use efficiency, generating positive yield response at rates as high as 450 kg N ha −1 sufficient to outweigh accompanying increases in N‐induced emissions for most impact categories. Thus, within the biofuel life cycle, trade‐offs across productivity, GHG intensity, and pollutant loads may be possible to avoid. However, adverse trade‐offs were seemingly unavoidable when impacts from E85 were compared to those of conventional gasoline, with E85 reducing GHG intensity but increasing local air and water pollutant loads relative to gasoline.